Determination of mercury species in natural waters at picogram level with on-line RP C18 preconcentration and HPLC-UV-PCO-CVAAS - Falter, Ralf; Schöler, Heinz Friedrich (Fresenius' journal of analytical chemistry, 1995)
A new technique has been developed for the determination of methyl-, ethyl-, methoxyethyl-, ethoxyethyl-, phenyl- and inorganic mercury in natural water samples. The mercury compounds have been complexed for the preconcentration on RP C18 columns by sodium pyrrolidinedithiocarbamate (SPDC), sodium diethyldithiocarbamate (SDDC) and hexamethyleneammonium (HMA) — hexamethylenedithiocarbamate (HMDC), separated by HPLC and determined by UV-PCO-CVAAS (ultra violet, post column oxidation, cold vapour atomic absorption spectrometry). The standard deviations are in the range of 6.9 to 11.8%. The recoveries amount to 86%, 78%, 88%, 83%, 79% and 84% for methyl-, ethyl-, methoxyethyl-, ethoxyethyl-, phenyl- and inorganic mercury for the enrichment from 300 ml water samples. The detection limit for methyl mercury is 0.5 ppt. This new on-line preconcentration procedure has been tested with rain, drinking, surface and process water samples.